Microstructure Evolution and Corrosion Resistance Evaluation of 17-4 Precipitation Hardening Stainless Steel Processed by Laser Powder Bed Fusion - Kugelmeier, C. L. (2024)
Precipitation hardening (PH) martensitic stainless steels, such as 17-4, have been investigated for use in additive manufacturing (AM) techniques to produce parts with complex and individualized geometries, finding wide use in the aerospace, petrochemical, nuclear, and marine industries due to their high mechanical strength and corrosion resistance. However, AM can result in a material with the presence of porosities, segregations and metastable phases. Thus, the aim of this research is to study the microstructure evolution and corrosion resistance of 17-4 PH processed by laser powder bed fusion (LPBF) in comparison with conventional processing, under thermal treatment, as-built, and after AM processing with thermal treatment conditions. The findings of this study show that the AM-processed material exhibits a microstructure with a fish scale-like morphology, smaller grain size and higher fraction of retained austenite, characteristics that are modified after solubilization treatment, although the hardness remains higher than that observed in conventional processing. The corrosion test results showed that the samples treated after AM processing present a corrosion resistance close to the samples only thermally treated.